Insecticidal Activity of Piperine Isolated from Piper sarmentosum - Gang, Feng; Huochun, Ye; Enlin, Yuan; Jing, Zhang; Chao, Yan; Qian, Jin; Zhengqiang, Peng; Yueguan, Fu (Plant Diseases and Pests(植物病虫害研究：英文版), 2014)
In order to clarify the insecticidal active ingredients of Piper sarmentosum,one active ingredient was isolated from ethanol extract of P. sarmentosum by bioassay-guided fractionation method. Its chemical structures were identified to be piperine by MS,1H NMR,13C NMR. The insecticidal activity of piperine and ethanol extract of P. sarmentosum against Aleurodicus dispels Russell were tested by leaf dip method. The results showed that piperine and ethanol extract of P. sarmentosum exhibited strong insecticidal activity against adults and nymphs of A. dispels; LC50values against adults were 28. 59 and 224. 31 mg/L,and LC50values against nymphs were 65. 91 and 336. 68 mg/L,respectively. There was no significant difference between piperine and azadirachtin against adults and nymphs of A.dispels. Therefore,piperine might be one of the main insecticidal ingredients of P. sarmentosum. In addition,piperine and ethanol extract showed ovicidal activity with different mode of action,piperine reduced the survival rate of newly hatched nymphs while ethanol extract impacted hatch of eggs.